A Gendered Analysis of Emotional Intelligence in the Workplace: Issues and Concerns for Human Resource Development. (June 2013) - Thory, Kathryn
Drawing on a sociological analysis considering gender, this article explores how emotional intelligence (EI) abilities are socially constructed and valued. It presents a range of societal trends including "the future is female" to explore how both men and women are perceived and judged against symbolic representations of masculine and feminine when they perform gendered conceptions of EI. The article illuminates how women and men may be encouraged to take up feminine and masculine interpretations of EI skills but women fare less well. It then examines the effects of EI's assessment and therapeutic methods in training and work-based use. It argues that these approaches are damaging to individuals when deployed in work environments where masculinized management resides as the dominant framework. Finally, the article discusses the findings in relation to HRD to reveal important theoretical guidelines for practice.